APLIKASI PENGAMANAN FILE BERTIPE *.PDF PADA VIDEO *.MP4 MENGGUNAKAN KRIPTOGRAFI VERNAM CIPHER DAN STEGANOGRAFI END of FILE - Mulatifa Laliha; Sutardi Sutardi; Natalis Ransi (Informatics Engineering Department of Halu Oleo University, 2019)
Security and confidentiality of messages in the communication process between the sender and receiver is an important thing that must be maintained so that the message would be difficult if not known by unauthorized parties. Cryptography Vernam Cipher is symmetric cryptography that used one time for a message and not reused. Steganography End of File (EoF) is one technique to insert data at the end of the file. Combine Vernam Cipher cryptography and EoF steganography on this research with a case study how the implementation of the security of *.pdf files on *.mp4 video. Based on the test results of *.pdf file encryption and steganography in video *.mp4 successfully performed on the size of small file size for use Vernam Cipher cryptography, plaintext length, and key length must be the same length, so that for large files will take a long time. The results of stegano show that the video files look like the original video can be viewed directly without that already is inserted in the video *.pdf, for EoF does not affect the quality of the video. It is concluded that the incorporation of Vernam Cipher Cryptography and EoF steganography successfully, where the process of implementing the algorithms when combined requires an average time of 65 seconds on the side Vernam Cipher cryptographic application due to the type of encryption key length is equal to the length of the plaintext. Keywords—End of File, Cryptography, Steganography, Vernam CipherDOI : 10.5281/zenodo.3253459